2017
DOI: 10.1108/nfs-06-2017-0114
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of risk factors of cardiovascular diseases among prisoners: a systematic review

Abstract: Purpose -Cardiovascular diseases threaten the global health system and their prevalence among the incarcerated population poses a huge economic burden to governments. The purpose of this paper is to investigate the prevalence of cardiovascular disease risk factors among prisoners.Design/methodology/approach -A systematic review was done on published studies that looked at prevalence and risk factors of cardiovascular disease among either male or female prisoners or both. PubMed, PubMed Central, Google scholar,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 46 publications
(107 reference statements)
1
10
0
Order By: Relevance
“…Similar data were obtained in the Warsaw Detention Center, where 43.4% of prisoners had excessive body weight [12]. Based on the results of 11 studies published in 2012-2015, Agyapong et al [31] indicated the problem of overweight and obesity in 35.6% and 23.3% of prisoners, respectively. However, prisoners are less frequently overweight than the general population [32,33].…”
Section: Discussionsupporting
confidence: 54%
“…Similar data were obtained in the Warsaw Detention Center, where 43.4% of prisoners had excessive body weight [12]. Based on the results of 11 studies published in 2012-2015, Agyapong et al [31] indicated the problem of overweight and obesity in 35.6% and 23.3% of prisoners, respectively. However, prisoners are less frequently overweight than the general population [32,33].…”
Section: Discussionsupporting
confidence: 54%
“…Compared with the average weight gain of the middle-aged US population, estimated to be between 0.5 and 1 kg/year, 51 the mean weight gain found in this review was up to five times higher in the first 2 years of imprisonment. Hypothesised reasons for this include a combination of a sedentary lifestyle and a poor diet (the high calorie meals served in prison and the extra snacks or sweet beverages purchased from the commissary store), 11 52 53 forced smoking cessation (which has been associated with weight gain 54 ), a high prevalence of people in prison taking psychotropic medication (known to affect weight), 11 high rates of depressive symptoms 55 and high levels of stress. 56 Many of these factors are interconnected which might create a vicious cycle of weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…served in prison and the extra snacks or sweet beverages purchased from the commissary store), 11 52 53 forced smoking cessation (which has been associated with weight gain 54 ), a high prevalence of people in prison taking psychotropic medication (known to affect weight), 11 high rates of depressive symptoms 55 and high levels of stress. 56 Many of these factors are interconnected which might create a vicious cycle of weight gain.…”
Section: Weight and Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Bai et al (2015) found that respiratory and cardiovascular problems were the most prevalent conditions in two New York State maximum-security prisons, with increased prevalence among Black individuals. Additionally, the highest rates of diabetes mellitus, cardiovascular conditions, liver disease, asthma, and sexually transmitted infections exist among incarcerated individuals over 40 years of age (Agyapong et al, 2017; Bai et al, 2015). These conditions alone make it more likely that an individual will experience complications if they are exposed to COVID-19 and in combination with age, make those individuals’ prognoses more dire.…”
Section: Incarcerated and At-riskmentioning
confidence: 99%